2018
DOI: 10.3389/fneur.2018.00515
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Characterization of Patients With Focal Epilepsy Using a Customized Targeted Resequencing Gene Panel

Abstract: Objective: Focal epilepsy is the most common subtype of epilepsies in which the influence of underlying genetic factors is emerging but remains largely uncharacterized. The purpose of this study is to determine the contribution of currently known disease-causing genes in a large cohort (n = 593) of common focal non-lesional epilepsy patients.Methods: The customized focal epilepsy gene panel (21 genes) was based on multiplex polymerase chain reaction (PCR) and sequenced by Illumina MiSeq platform.Results: Eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Using a broad exome-based approach, we identified molecular diagnoses in 12%, which is less than in syndromic epilepsies,13 but comparable to the small-scale study by Perucca et al evaluating diagnostic ES with targeted gene analysis in NAFE 14. In contrast, our diagnostic yield is remarkably higher than that reported by Hildebrand et al and Tsai et al , who found diagnostic variants in only 0.8% and 1.85% of cases, respectively 15 16. First, the lower hit rate may be explained by the broader inclusion criteria of these studies, not accounting for age of onset and a positive family history.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Using a broad exome-based approach, we identified molecular diagnoses in 12%, which is less than in syndromic epilepsies,13 but comparable to the small-scale study by Perucca et al evaluating diagnostic ES with targeted gene analysis in NAFE 14. In contrast, our diagnostic yield is remarkably higher than that reported by Hildebrand et al and Tsai et al , who found diagnostic variants in only 0.8% and 1.85% of cases, respectively 15 16. First, the lower hit rate may be explained by the broader inclusion criteria of these studies, not accounting for age of onset and a positive family history.…”
Section: Discussionsupporting
confidence: 77%
“…One small-scale diagnostic ES study used a targeted analysis approach in 40 patients with NAFE and a suspected genetic background, resulting in a diagnostic yield of 12.5% 14. Two further studies used narrower panel approaches limited to known focal epilepsy genes, both resulting in hit rates of only less than 2% 15 16. These contrasting findings demonstrate the uncertainty about genetic testing outcomes for this relevant epilepsy subgroup, and there is a strong need to evaluate comprehensive genetic–diagnostic approaches in clinically well-characterised cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Family B was diagnosed through a microfluidic multiplex polymerase chain reaction–based multigene panel (Fluidigm Access 48.48 Array). Amplified products were barcoded and sequenced using an Illumina MiSeq system followed by standardized bioinformatic analysis and Sanger sequencing . The functional impact of variant was predicted using Polymorphism Phenotyping 2 (PolyPhen‐2; http://genetics.bwh.harvard.edu/pph2/), Protein Variation Effect Analyzer (PROVEAN; http://provean.jcvi.org/index.php), and MutationTaster (http://www.mutationtaster.org).…”
Section: Methodsmentioning
confidence: 99%
“…Amplified products were barcoded and sequenced using an Illumina MiSeq system followed by standardized bioinformatic analysis and Sanger sequencing. 19,20 The functional impact of variant was predicted using Polymorphism Phenotyping 2 (PolyPhen-2; http://genetics.bwh.harvard.edu/ pph2/), 21 Protein Variation Effect Analyzer (PROVEAN; http://provean.jcvi.org/index.php), 22 and MutationTaster (http://www.mutationtaster.org). 23 Segregation analysis was performed in the family members where DNA samples were available.…”
Section: Clinical and Molecular Genetic Studymentioning
confidence: 99%
“…La encefalopatía epiléptica infantil precoz 9 o epilepsia restringida a mujeres con o sin retraso mental, es causada por una mutación en el gen que codifica la proteína protocadherina-19 (PCDH19; 300460) en el cromosoma Xq22 1-2 . Identificándose en la actualidad 6 mutaciones diferentes en el gen PCDH19 3 .Caracterizado fenotípicamente por encefalopatía epiléptica temprana, múltiples tipos de crisis, asociados con fiebre, retraso mental leve a severo con trastorno del lenguaje y ataxia 4 .Las mutaciones en PCDH19 pueden causar una encefalopatía epiléptica temprana y grave que simula el Síndrome de Dravet, con características clínicas muy similares, incluida la asociación de convulsiones tempranas febriles y afebriles, polimorficas, en salvas, retraso en el desarrollo y el lenguaje, alteraciones del comportamiento y regresión cognitiva 5 .…”
Section: Introductionunclassified